Efektivitas Atraktan terhadap Daya Tetas dan Jumlah Telur Nyamuk Aedes albopictus di Laboratorium - Muhammad Rasyid Ridha; Abdullah Fadilly; Budi Hairani; Wulan RSG Sembiring; Gusti Meliyanie (Loka Litbang Kesehatan Pangandaran, 2019)
Abstract. Aedes albopictus can act as a primary or secondary vector of dengue hemorrhagic fever andchikungunya. Its population needs to be controlled. One of the environmentally-friendly control methods isthe use of ovitrap. Ovitrap will be more optimal if it added by attractant substances from easily obtainedingredients in the surrounding environment. This study aims to determine the effectiveness of attractants inthe form of water-soaked paddy (Oryza sativa), cogongrass (Imperata cylindrica) and Indian goosegrass(Eleusine indica). An experimental study with a completely randomized design (CRD) was carried out at theEntomology Laboratory of Balai Litbangkes Tanah Bumbu in January - April 2018. The population of thisstudy is the 10th filial of Ae. albopictus laboratory colonization and gravid female mosquito as samples.Material combination in the study was paddy straw soaking water (ARJP), Indian goosegrass immersionwater, cogongrass soaking water, Ae albopictus used eggs laying water (ABT), and distilled water as control(K). Repetition was done five times. Effectiveness of attractants analyzed by ANOVA and LSD tests. Datanormality tested by Kolmogorov-Smirnov test, if it was not fulfilled, the Kruskal Wallis test was used. Theresults showed that the use of attractants of water-soaked paddy, Indian goosegrass and cogongrass provedto have a different effect on the number of Aedes albopictus mosquito eggs compared to aquades and eggslaying water, but there was no influence between the three types of attractants.